TECHNICAL AND ECONOMIC OPTIMIZATION OF COGENERATION TECHNOLOGY USING COMBUSTION AND GASIFICATION - Lisý, Martin; Baláš, Marek; Špiláček, Michal; Skála, Zdenek (Acta Polytechnica, 2014)
This paper presents the technical and economic optimization of new microcogeneration technology with biomass combustion or biomass gasification used for cogeneration of electrical energy and heat for a 200 kW unit. During the development phase, six possible connection solutions were investigated, elaborated and optimized. This paper presents a basic description of the technology, a description of the technological solutions, and especially the results of balance and financial calculations, ending with a comparison and evaluation of the results.